2019
DOI: 10.1016/j.isci.2019.09.009
|View full text |Cite
|
Sign up to set email alerts
|

SIDT2 RNA Transporter Promotes Lung and Gastrointestinal Tumor Development

Abstract: SummaryRNautophagy is a newly described type of selective autophagy whereby cellular RNAs are transported into lysosomes for degradation. This process involves the transmembrane protein SIDT2, which transports double-stranded RNA (dsRNA) across the endolysosomal membrane. We previously demonstrated that SIDT2 is a transcriptional target of p53, but its role in tumorigenesis, if any, is unclear. Unexpectedly, we show here that Sidt2−/− mice with concurrent oncogenic KrasG12D activation develop significantly few… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…Lastly, in order to further verify the expression status of altered RBPs in pancreatic cancer cell lines and tissue samples, we explored the published literature and used The Protein Atlas data. There were multiple studies where actually the expression of these specific RBPs was estimated in several pancreatic cancer cell lines or patient tissues using qPCR and/or Western blotting or immunohistochemical analysis; convincingly supporting our results ( Supplementary Table S8 ) ( Fernández-Salas et al, 2000 ; Kong et al, 2010 ; Bhatti et al, 2011 ; Taniuchi et al, 2014a ; Cai et al, 2015 ; Taniuchi et al, 2015 ; Schultz et al, 2017 ; Tang et al, 2017 ; Yu et al, 2017 ; Nguyen et al, 2019 ; Cui et al, 2020 ; Konishi et al, 2021 ). Immunohistochemistry results for IGF2BP3, PAIP2B, and SIDT2 have already been shown in Figure 2 , and we additionally present the results for the rest of the five RBPs in pancreatic cancer tissues as shown in Supplementary Figure S4 , which strongly validate their expression in patient samples signifying their importance in the disease.…”
Section: Resultssupporting
confidence: 86%
“…Lastly, in order to further verify the expression status of altered RBPs in pancreatic cancer cell lines and tissue samples, we explored the published literature and used The Protein Atlas data. There were multiple studies where actually the expression of these specific RBPs was estimated in several pancreatic cancer cell lines or patient tissues using qPCR and/or Western blotting or immunohistochemical analysis; convincingly supporting our results ( Supplementary Table S8 ) ( Fernández-Salas et al, 2000 ; Kong et al, 2010 ; Bhatti et al, 2011 ; Taniuchi et al, 2014a ; Cai et al, 2015 ; Taniuchi et al, 2015 ; Schultz et al, 2017 ; Tang et al, 2017 ; Yu et al, 2017 ; Nguyen et al, 2019 ; Cui et al, 2020 ; Konishi et al, 2021 ). Immunohistochemistry results for IGF2BP3, PAIP2B, and SIDT2 have already been shown in Figure 2 , and we additionally present the results for the rest of the five RBPs in pancreatic cancer tissues as shown in Supplementary Figure S4 , which strongly validate their expression in patient samples signifying their importance in the disease.…”
Section: Resultssupporting
confidence: 86%
“…We identified SIDT2 as a potential target of miR-210-5p using a bioinformatics approach. SIDT2 is a lysosomal integral membrane protein that is widely expressed in mammalian tissue (27,28). Previous studies have revealed that SIDT2 mediated an array of cellular biological responses, including autophagy, lipid metabolism, inflammation, and insulin sensitivity (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the specific interaction of IL1β- mRNA was mediated by ZC3H12D protein, which recognizes its 3′ - UTR; this is not surprising, as many mRNA-binding proteins bind to secondary structures, including stem loops and short consensus sequences, such as AREs, which are situated in the 3′ - UTR of many transcripts in the cytoplasm 32 . Also, extracellular double-stranded RNA is nonspecifically recruited into the cytoplasm by the S1D family, resulting in the usage of cellular RNA interference silencing 52 54 . So far, several types of RNA uptake inside cells have been reported, and some of them are utilized in gene therapies 55 .…”
Section: Discussionmentioning
confidence: 99%